The genetics and genomics of the rabbit - Fontanesi, Luca (CAB International, 2021)
"Covering all aspects of the genetics and genomics of the rabbit, this book includes domestication, classical genetics, the rabbit genome, genetic maps and markers, coat colour genetics, immunogenetics, transgenic rabbits and biotechnology applications. It also covers the genetics of meat and fibre production, reproduction and disease resistance"--